The Feasibility of Increasing Lipid Extraction in Tilapia (Oreochromis niloticus) Waste by Proteolysis. Issue 2 (17th February 2016) - Shirahigue, Ligianne Din; Silva, Maira Oliveira; Camargo, Aline Cristina; Sucasas, Lia Ferraz de Arruda; Borghesi, Ricardo; Cabral, Ingridy Simone Ribeiro; Savay-da-Silva, Luciana Kimie; Galvão, Juliana Antunes; Oetterer, Marília
ABSTRACT: The aim of the present study was to evaluate the feasibility of increasing lipid extraction in tilapia ( Oreochromis niloticus) waste using different enzymes and to minimize the periods of hydrolysis to evaluate the performance of the lipid fractions. When processing waste tilapia, commercial enzymes were added that were composed of neutrase and alcalase acting at different hydrolysis times to produce the best yields. The treatment proved feasible for obtaining the protein hydrolysates. The type of enzyme and the hydrolysis time determined the degree of fractionation. The enzymes performed well, and the highest efficiency occurred within 2 h of hydrolysis. By fractionating, the obtained by-products can be applied in the preparation of feed, as the lipid fraction treatments yielded significant amounts of polyunsaturated fats and suitable n-6/n-3 ratios.